A classic twin study of lower urinary tract obstruction: Report of 3 cases and literature review. Issue 2 (17th April 2018) - Frese, Sandra; Weigert, Alexander; Hoppe, Bernd; Feldkötter, Markus; Ludwig, Michael; Weber, Stefanie; Kiliś‐Pstrusińska, Katarzyna; Zaniew, Marcin; Reutter, Heiko; Hilger, Alina C.
Abstract : Objective: The aim of the present study was to investigate genetic effects in the formation of congenital lower urinary tract obstruction (LUTO) comprising posterior urethral valves (PUV), urethral atresia, and urethras with variable degrees of stenosis. Methods: A classic twin study was performed by assessing LUTO twin pairs from the literature. Furthermore, data regarding 3 previously unreported twin pairs with PUV from University of Bonn, Essen and Wrocławs own in‐house databases were added. Both pair‐ and probandwise concordance rates were calculated and compared for monozygotic (MZ) and dizygotic (DZ) twin pairs. Results: The pairwise concordance rates for all LUTO were 53% (95% confidence interval [CI] 32%–73%) and 17% (95% CI 3%–56%) for MZ and DZ twin pairs, respectively ( P  = .180). The probandwise concordance rates were 69% (95% CI 51%–83%) and 29% (CI 95% 8%–64%) for MZ and DZ twin pairs respectively ( P  = .084). The MZ/DZ ratios of the pair‐ and probandwise concordance rates were 3.1 and 2.4, respectively. Conclusion: The present study did not show significant differences in comparisons of concordance rates of MZ and DZ twin pairs, probably due to the small number of twin pairs reported. However, the more than 2‐fold higher pair‐ and probandwise concordance rates for MZ versus DZ twin pairs are very suggestive of a contribution of genetic factors to the development of LUTO.